2021
DOI: 10.1096/fj.202001629rr
|View full text |Cite
|
Sign up to set email alerts
|

Chemical‐based primary human hepatocyte monolayer culture for the study of drug metabolism and hepatotoxicity: Comparison with the spheroid model

Abstract: Traditionally cultured monolayers of primary human hepatocytes (PHHs) deteriorate within days and thereby become unsuitable for drug‐related studies. PHH spheroids (3D PHHs) maintain liver functions for weeks, but are considerably more demanding. Recently, a chemical‐based approach (5C PHHs) succeeded in long‐term culture of hepatocyte monolayers, but it remains unclear whether the drug‐related functions are preserved. To clarify this, we compared the 5C and 3D PHHs in terms of gene expression analysis, proteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Monolayer 2D culture systems using immortalized cell lines and primary hepatocytes have been widely used for liver toxicity testing [ 8 ]. However, 2D culture systems cannot recapitulate the liver microenvironments that are strongly correlated with hepatic cellular functions; hepatocytes in monolayer 2D culture systems lose viability rapidly and decrease liver-specific functionality within a few days [ 11 , 12 , 13 ]. A sandwich-culture system of culturing primary hepatocytes between two layers of collagen improved cell viability, polarized architecture, and liver-specific functions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monolayer 2D culture systems using immortalized cell lines and primary hepatocytes have been widely used for liver toxicity testing [ 8 ]. However, 2D culture systems cannot recapitulate the liver microenvironments that are strongly correlated with hepatic cellular functions; hepatocytes in monolayer 2D culture systems lose viability rapidly and decrease liver-specific functionality within a few days [ 11 , 12 , 13 ]. A sandwich-culture system of culturing primary hepatocytes between two layers of collagen improved cell viability, polarized architecture, and liver-specific functions [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…3D spheroid PHHs retain the in vivo hepatic phenotype of human liver in culture for several weeks and stably express CYPs and transporters, which is a prerequisite for in vitro to in vivo extrapolation. 15,16,18,19,24 Previously, it was shown that high baseline expression of CYP3A4 mRNA in 3D spheroid PHHs resulted in clinically more relevant magnitude of induction than in 2D monolayer PHHs. 23 Moreover, 3D spheroid PHHs were able to identify inducers that failed to induce CYP3A4 in 2D monolayer PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…16,24 3D spheroid PHHs have outperformed 2D monolayer and sandwich cultured PHHs in hepatotoxicity assays 15,20 and they retain drug metabolism activity of important CYPs for several weeks allowing long-term experiments. 15,16,18,19,24,25 Assessment of drug clearance and identification of low-abundant metabolites is also feasible in 3D spheroid PHHs. 22,25,26 In contrast to 2D monolayer PHHs, 3D spheroid PHHs express CYP3A4 mRNA at almost 200-fold higher levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations